2013
DOI: 10.1371/journal.pone.0063174
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Community-Based Approaches Doubled Tuberculosis Case Notification and Improve Treatment Outcome in Southern Ethiopia

Abstract: BackgroundTB Control Programmes rely on passive case-finding to detect cases. TB notification remains low in Ethiopia despite major expansion of health services. Poor rural communities face many barriers to service access.Methods and FindingsA community-based intervention package was implemented in Sidama zone, Ethiopia. The package included advocacy, training, engaging stakeholders and communities and active case-finding by female Health Extension Workers (HEWs) at village level. HEWs conducted house-to-house… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
229
2
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 154 publications
(252 citation statements)
references
References 11 publications
15
229
2
2
Order By: Relevance
“…However, it is important to emphasise that our description is not universal and individual examples of enabling practices and trial capacity exist. Furthermore, no information was available to us on the number of trial applications, rejections and turnaround times and although little local evidence-based practice was reported, this was not confirmed by the authorities and examples of local trials influencing policy are found in the literature 23. Nevertheless these results demonstrate the importance of taking a system-wide view to research development.…”
Section: Discussionmentioning
confidence: 87%
“…However, it is important to emphasise that our description is not universal and individual examples of enabling practices and trial capacity exist. Furthermore, no information was available to us on the number of trial applications, rejections and turnaround times and although little local evidence-based practice was reported, this was not confirmed by the authorities and examples of local trials influencing policy are found in the literature 23. Nevertheless these results demonstrate the importance of taking a system-wide view to research development.…”
Section: Discussionmentioning
confidence: 87%
“…Community-based ICF interventions implemented elsewhere in India and other countries have shown similar results; this reflects the replicability and scalability of such interventions. [3][4][5] An intervention in Orissa, India, increased case detection by 11%. 3 A similar ICF activity conducted in Ethiopia doubled the pulmonary TB case notification rate, from 64 to 127/100 000 population/year.…”
Section: Public Health Actionmentioning
confidence: 99%
“…3 A similar ICF activity conducted in Ethiopia doubled the pulmonary TB case notification rate, from 64 to 127/100 000 population/year. 4 In the results of the FIDELIS (Fund for Innovative DOTS Expansion through Local Initiatives to Stop TB) project in China, which massively mobilised school students for case finding, the case detection in intervention counties increased by a factor of 3.5 relative to the pre-intervention period. 5 There were some limitations to our study.…”
Section: Public Health Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was then subsequently scaled up nationwide and a 100% geographical and 92% health facility coverage were achieved [2]. Nonetheless, previous studies conducted in different regions of Ethiopia showed that the passive case finding approach, where TB patients self-report to health care facilities leaves significant number of undiagnosed TB cases in the community [5]- [9].…”
Section: Introductionmentioning
confidence: 99%